Grammtical Code Switching in The English Department Proposal Seminar - Rakhmat Wahyudin Sagala; Tri Indah Rezeki (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2018)
The fundamental characteristics of the lecturers and the students in the English Department should use English. Lack of English competence is widely considered to be the major cause of code switching. The aim of our work to broaden current knowledge of the phenomenon of grammatical code switching in the English Department proposal seminar at STKIP Budidaya Binjai. This study applied descriptive qualitative research with the data from the utterances of the lecturers and the students during the process of proposal seminar. The data were obtained from observation, interview, and field note. Grammatical code switching in the English Department proposal seminar were tag code switching consisted of 12 utterances, inter-sentential code switching consisted of 15 utterances, intra-sentential code switching consisted of 19 utterances, proper noun and noun phrase consisted of 7 utterances, negative words consisted of 4 utterances, languages similarity consisted of 11 utterances and discourse marker consisted of 16 utterances. It can be concluded that grammatical code switching occurs in the English Department proposal seminar process